The Longitudinal Association between Self–Esteem and Depressive Symptoms in Adolescents: Separating Between–Person Effects from Within–Person Effects. Issue 6 (November 2018) - Masselink, M.; Van Roekel, E.; Hankin, B.L.; Keijsers, L.; Lodder, G.M.A.; Vanhalst, J.; Verhagen, M.; Young, J.F.; Oldehinkel, A.J.
Many longitudinal studies have investigated whether self–esteem predicts depressive symptoms (vulnerability model) or the other way around (scar model) in adolescents. The most common method of analysis has been the cross–lagged panel model (CLPM). The CLPM does not separate between–person effects from within–person effects, making it unclear whether the results from previous studies actually reflect the within–person effects or whether they reflect differences between people. We investigated the associations between self–esteem and depressive symptoms at the within–person level, using random intercept cross–lagged panel models (RI–CLPMs). To get an impression of the magnitude of possible differences between the RI–CLPM and the CLPM, we compared the results of both models. We used data from three longitudinal adolescent samples (age range: 7–18 years; study 1: N = 1948; study 2: N = 1455; study 3: N = 316). Intervals between the measurements were 1–1.5 years. Single–paper meta–analyses showed support for small within–person associations from self–esteem to depressive symptoms, but not the other way around, thus only providing some support for the vulnerability model. The cross–lagged associations in the aggregated RI–CLPM and CLPM showed similar effect sizes. Overall, our results show that over 1– to 1.5–year time intervals, low self–esteem may negatively influence depressive symptoms over time within adolescents, but only weakly so. © 2018 The Authors. European Journal of Personality published by John Wiley & Sons Ltd on behalf of European Association of Personality Psychology